2001
DOI: 10.1124/mol.60.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cellular Invasion by Activated G-Protein Subunits Gαo, Gαi1, Gαi2, and Gαi3 and Sequestration of Gβγ

Abstract: It was shown previously that platelet-activating factor receptors (PAF-Rs) inhibit invasiveness of colonic and kidney epithelial cells induced by the src and Met oncogenes via a pertussis toxin-sensitive mechanism. Therefore, Madin-Darby canine kidney (MDCKts.src) cells were stably transfected with constitutively activated forms of Galphao, Galphai1, Galphai2, Galphai3 (AGalphao/i), two Gbetagamma sequestering proteins [C-terminal end of beta-adrenergic receptor kinase (ct-betaARK) and the Galphat subunit of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Instead, disruption of G␤␥ signaling inhibits neutrophil chemotaxis (Lehmann et al, 2008). In addition, sequestration of G␤␥ subunits or using constitutively activated G i ␣ subunit suppress cellular invasion of Madin-Darby canine kidney cells, suggesting that only G␤␥ signaling is responsible for cell invasion (Faivre et al, 2001). Thus, we hypothesized that G␤␥ signaling is important for breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, disruption of G␤␥ signaling inhibits neutrophil chemotaxis (Lehmann et al, 2008). In addition, sequestration of G␤␥ subunits or using constitutively activated G i ␣ subunit suppress cellular invasion of Madin-Darby canine kidney cells, suggesting that only G␤␥ signaling is responsible for cell invasion (Faivre et al, 2001). Thus, we hypothesized that G␤␥ signaling is important for breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell invasion assays were done using collagen type I gels and parental or stably transfected colorectal, kidney, and lung cell lines as described previously (18,29,30). This assay is based on counting the percentage of invasive cells in collagen type I versus total number of viable cells in the same field.…”
Section: Methodsmentioning
confidence: 99%
“…Zeiger et al (16) first showed in vivo that constitutive activation of Ga by a transgene expressing the cholera toxin A1 subunit in normal cells induced the mitotic activity, infiltration of skeletal muscle, and lung metastases. Recent research shows that Ghg dimers are also involved in cancer transformation and invasive tumor growth because forced expression of Ghg-sequestering agents, such as the COOH terminus of G-protein-coupled receptor kinase 2 (ct-hARK), obliterates multiple oncogenic pathways (17,18). Conversely, overexpression of Ghg subunits and constitutively active mutants of Ga subunits stimulates mitogen-and stress-activated protein kinase cascades p42/p44, p38, and c-Jun NH 2 -terminal kinase, which regulate promoter activity of immediate response genes involved in cell proliferation, apoptosis, and transformation (19).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cell invasion is facilitated by myofibroblastderived proteinases, which also serve structural remodelling of the ECM and so excitation of nociceptors. Remarkably, both stimulation of cancer cell invasion and pain signalling by nociceptors involve signalling pathways that are activated by heterotrimeric guanine nucleotide-binding protein (G-protein)-coupled receptors [151,152]. Such receptors, of which more than 100 are known in mammalian cells, are targets for hormones, neurotransmitters, chemokines, local mediators, and sensory stimuli.…”
Section: Myofibroblasts and Cancer Painmentioning
confidence: 99%